2023
DOI: 10.3389/fenvs.2023.1179419
|View full text |Cite
|
Sign up to set email alerts
|

The effect of digitalization transformation on greenwashing of Chinese listed companies: an analysis from the dual perspectives of resource-based view and legitimacy

Abstract: Background: The goal of “peak carbon and carbon neutrality” has pointed out the direction for the digital transformation (DIT) of enterprises. Companies need to pay a price when they seek green development or fulfill environmental responsibility. Out of self-interest, enterprises may exaggerate their environmental performance (EP) and then greenwashing behavior appears. Whether DIT can curb greenwashing behavior is a topic worth discussing.Objective: This paper proposes a theoretical framework for the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…Misleading claims about environmentally friendly products can undermine responsible consumption efforts; verifying the accuracy of such claims requires reliable data protection [139]. Zhang et al found that digital transformation (DIT) can curb greenwashing behavior by enterprises, and government subsidies, resource slack, and public pressure positively moderate the relationship [140]. Ramtiyal et al studied the impact of greenwashing by corporations on consumers' sustainable purchase behavior and found that corporate greenwashing has a negative effect on sustainable consumer behavior [141].…”
Section: Digital Greenwashingmentioning
confidence: 99%
“…Misleading claims about environmentally friendly products can undermine responsible consumption efforts; verifying the accuracy of such claims requires reliable data protection [139]. Zhang et al found that digital transformation (DIT) can curb greenwashing behavior by enterprises, and government subsidies, resource slack, and public pressure positively moderate the relationship [140]. Ramtiyal et al studied the impact of greenwashing by corporations on consumers' sustainable purchase behavior and found that corporate greenwashing has a negative effect on sustainable consumer behavior [141].…”
Section: Digital Greenwashingmentioning
confidence: 99%
“…Only a few studies have considered organizational slack as a contextual factor. Some studies find that slack resources can moderate the impact of digitalization, for example, Zhang K. et al (2023) found that slack resources can positively moderate the inhibition effect of digital transformation on greenwashing behavior. In contrast, others examine how the direction or degree of influence of organizational or environmental factors on firm greening changes with variations in slack resources.…”
Section: Introductionmentioning
confidence: 99%